Effects of cane peeling and aqueous extraction on compatibility of two rattan species with portland cement (2008)
Rattan cane is a relatively abundant lignocellulosic in Africa and Asia that could be used for wood-cement composite production. However, rattans tend to inhibit cement setting. This study investigated the effects of cane peeling and aqueous extraction on maximum hydration temperature (Tmax) and setting time (tmax) rattan-cement- water systems using Calamus deerratus and Lacosperma secundiflorum rattan species. Peeling was done manually to remove the silified epidermis before hammer-milling to obtain cane particles. Portions of the particles were soaked in de-ionised cold (25oC) and hot water (800C) respectively for 30 minutes. Findings showed that aqueous extraction improved the Tmax and reduced the tmax of the rattan-cement mixtures while peeling caused reduction in both Tmax and tmax. The two rattan species seemed more amenable to cold rather than hot water extraction. Peeling, species, aqueous pre-treatment and their interactions had significant effects on the setting time of the rattan-cement mixtures.